Novelty acquisition is associated with induction of hippocampal long-term depression - Manahan-Vaughan, Denise (The National Academy of Sciences, 1999)
Homosynaptic long-term depression (LTD) consists of a persistent nonpathological decrease in synaptic transmission, which is induced by low-frequency stimulation. In vivo, low-frequency stimulation (1 Hz, 900 pulses) induces LTD in Wistar but not Hooded Lister rats. In this study, we investigated the influence of behavioral learning and behavioral state on the expression of LTD in both rat strains. Recordings were taken from freely moving animals that had undergone chronic implantation of a recording electrode in the hippocampal CA1 region and a bipolar stimulating electrode in the ipsilateral Schaffer collateral–commissural pathway. Exposure of the rat strains to stress induced a significant elevation in serum corticosterone levels but did not facilitate LTD expression. However, LFS given during exploration of a novel environment resulted in LTD expression in Hooded Lister, and LTD enhancement in Wistar, rats. Reexposure to the same environment did not result in new expression of LTD. Behavioral comparison between the first and second environmental exposure confirmed that the animals had habituated to the novel environment. These observations strongly implicate an association between novelty acquisition and LTD.